Considerations about enamel microabrasion after 18 years - Sundfeld, Renato Herman [UNESP]; Croll, Theodore P.; Briso, André Luiz Fraga [UNESP]; De Alexandre, Rodrigo Sversut; Neto, Daniel Sundfeld (My University, 2007)
Purpose: To review of the current status of enamel microabrasion method and its results 18 years after the development and application of this method. Methods: A technique performing enamel microabrasion with hydrochloric acid mixed with pumice and other techniques employing a commercially available compound of hydrochloric acid and fine-grit silicon carbide particles in a water-soluble paste have been described. Much has been learned about the application of this esthetic technique, long-term treatment results and microscopic changes to the enamel surface that has significant clinical implications. The latest treatment protocol is presented and photographic case histories document the treatment results. Clinical observations made over 18 years are discussed. Results: According to our findings, the dental enamel microabrasion technique is a highly satisfactory, safe and effective procedure.